Electrospun PVDF Membranes Incorporated with Functionalized Carbon-based Material for Removal of Cationic Dyes - Demirci, Fatma; Özsel, Burcak (My University, 2023)
In this study, polyvinylidene fluoride (PVDF) polymeric membranes with addition of functionalized carbon-based material (CBM) were fabricated by using electrospinning technique for the removal of cationic dyes from wastewater. CBM was prepared through a two-step carbonization process from cotton linter as an agricultural waste biomass. The characterization of CBM was performed by using Brunauer–Emmett–Teller (BET) surface analysis, fourier transform infrared spectrometry (FTIR) and elemental analysis. The morphologies of electrospun membranes were observed by scanning electron microscope (SEM) which clearly revealed that nanofibers with a smooth surface were produced by incorporation of CBM. According to the results obtained from FTIR and differential scanning calorimetry (DSC), crystallization behavior of PVDF membranes was promoted by increasing the percentage of CBM in the membrane. PVDF membrane prepared with the addition of 3 wt % CBM exhibited the highest water flux performance with a dye rejection of 74.6 % in comparison with the pure PVDF one.
Keywords: Dye removal; Electrospinning; membrane; carbon-based material